Evaluation of tracheal intubations in a paediatric intensive care unit - Laura Butragueño-Laiseca; Laura Torres; Elena O'Campo; Sara de la Mata Navazo; Javier Toledano; Jesús López-Herce; Santiago Mencía (Elsevier, 2023)
Introduction: Tracheal intubation is a frequent procedure in paediatric intensive care units (PICUs) that carries a risk of complications that can increase morbidity and mortality. Patients and methods: Prospective, longitudinal, observational study in patients intubated in a level III PICU between January and December 2020. We analysed the risk factors associated with failed intubation and adverse events. Results: The analysis included 48 intubations. The most frequent indication for intubation was hypoxaemic respiratory failure (25%). The first attempt was successful in 60.4% of intubations, without differences between procedures performed by staff physicians and resident physicians (62.5% vs 56.3%; P = .759). Difficulty in bag-mask ventilation was associated with failed intubation in the first attempt (P = .028). Adverse events occurred in 12.5% of intubations, and severe events in 8.3%, including 1 case of cardiac arrest, 2 cases of severe hypotension and 1 of oesophageal intubation with delayed recognition. None of the patients died. Making multiple attempts was significantly associated with adverse events (P < .002). Systematic preparation of the procedure with cognitive aids and role allocation was independently associated with a lower incidence of adverse events. Conclusions: In critically ill children, first-attempt intubation failure is common and associated with difficulty in bag-mask ventilation. A significant percentage of intubations may result in serious adverse events. The implementation of intubation protocols could decrease the incidence of adverse events. Resumen: Introducción: La intubación traqueal es un procedimiento frecuente en las unidades de cuidados intensivos pediátricos con riesgo de complicaciones que pueden aumentar la morbimortalidad. Pacientes y métodos: Estudio descriptivo y analítico de una cohorte prospectiva incluyendo a los pacientes intubados en una UCIP de tercer nivel entre enero y diciembre de 2020, analizando los factores asociados con el fracaso de intubación y los efectos adversos. Resultados: Se analizaron 48 intubaciones. La indicación más frecuente fue el fallo respiratorio hipoxémico (25%). El primer intento de intubación fue exitoso en el 60,4%, sin diferencias entre los médicos adjuntos 62,5% y los residentes 56,3%, p = 0,759. La dificultad en la ventilación con bolsa y mascarilla se asoció con el fracaso del primer intento de intubación (p = 0,028). Se objetivaron eventos adversos en un 12,5% de las intubaciones, siendo graves en un 8,3% de los casos, incluyendo una parada cardiorrespiratoria, dos casos de hipotensión grave y una intubación esofágica detectada de forma tardía. Los intentos múltiples de intubación se asociaron significativamente con la aparición de eventos adversos (p < 0,002). La preparación sistemática del procedimiento con ayudas cognitivas y asignación de los papeles del equipo se relacionó de forma independiente con un menor número de eventos adversos. Conclusiones: El éxito en el primer intento de intubación en niños en estado crítico es bajo y se relaciona con la dificultad de ventilación con bolsa y mascarilla. En un porcentaje significativo pueden presentar efectos adversos graves. La utilización de protocolos puede disminuir el número de eventos adversos.